The Case Study of Entry Strategies Amongst Wal-Mart, Carrefour, and Tesco - Chung, Chia-Lin (2011)
As the fundamental shift occurs in the world economy, we are moving toward a world in which barriers to cross-border trade and investment are declining, and national economies are merging into an interdependent, integrated global economic system, the process of globalisation is inevitable. This shifting phenomenon happens in different industries, and so as in retailing industry. The aim of the research is to analyse how market-based aspect and culture-based aspect determine the entry strategies for international enterprises by choosing the three largest retailer giants in the world as the research objectives. The applied theoretical framework in this study is the Uppsala model, which is proposed by Joahanson and Vahlne in 1977; and the five cultural dimensions, by Geert Hofstede (1984). The outcome of this study is conducted by examining and analysing the retailers performance in different regions both in the past and in the present.